Isolation and Biochemical Characterisation of Long-Tailed Macaque Aerobic Gut Bacteria from Tinjil Island, Indonesia (Indonesian Journal of Primatology, 2024)
Long-tailed macaque (Macaca fascicularis; LTM) is a common non-human primate used as an animal model in the medical field for its genetic similarity with humans. Maintaining the gut microbiota balance of LTM is crucial to avoid the possibility of disease in LTM caused by dysbiosis. Therefore, this study aims to isolate bacteria from the semi-wild LTM from Tinjil Island to know the diversity of their gut microbiota. We serially diluted four semi-wild LTM fecal samples and spread them onto the nutrient agar medium for bacteria enumeration through Total Plate Count (TPC). Then, we follow Bergey's Manual Determinative of Bacteriology. The bacteria isolates would be identified morphologically and biochemically. The average of total viable bacteria obtained was 1.86 x 109 CFU/g. Aerobic isolation of bacteria from all the samples resulted in 19 isolates of gram-positive bacteria, of which six putative species of Staphylococcus sp., three Bacillus sp., four Micrococcus sp., and four Corynebacterium sp. In general, isolating cultivable fecal microbiota from fecal samples of semi-wild LTM from Tinjil Island has provided an overview of its gut microbiota composition based on limited analytical methods using cultured-dependent methods.